Analisa Pengaruh Ground Vibration terhadap Stabilitas Low Wall Blok Muara Tiga Besar Utara Pit Timur Menggunakan Software GeoStudio 2012 di PT Bukit Asam (Persero) Tbk, Kabupaten Muara Enim - Deza Pahlevi Antasari; Irvani Irvani; Anisa Indriawati (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2017)
Ground vibration will produce variable Peak Particle Acceleration (PPA) which endanger the stability of the slope especially low wall. This study discusses the effect of ground vibration on the stability of the low wall and restricted in Block MTBU East Pit. While the slope analysis conducted by the method of Morgenstern-Price (1965) Manually and Software GeoStudio 2012, as well as statistical regression analysis approach in finding a relationship between the variables SD-PPA and PPA-FK. The higher the value of the PPA will lower prices Safety Factor (FK) of slope, proved to vibration FK 0.0133 g yield of 1.258 (C-C’) and 1.292 (D-D’), whereas the vibrations of 0.225 g yield of 0.771 FK (C- C’) and 0.768 (D-D’). The relationship between the scaled distance (SD) of the PPA produces non-linear relationship on a graph of power. The relationship between PPA against FK produces a linear relationship on the Section C-C’ and Section D-D’. The proposal obtained at a distance of 200 m from the blasting area 29.352 kg and at a distance of 500 m is 183.447 kg maximum load of explosives.